2012
DOI: 10.1371/journal.pone.0036530
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pathogenesis of Lung Adenocarcinoma Subtypes Involving Sequence Mutations, Copy Number, Chromosomal Instability, and Methylation

Abstract: BackgroundLung adenocarcinoma (LAD) has extreme genetic variation among patients, which is currently not well understood, limiting progress in therapy development and research. LAD intrinsic molecular subtypes are a validated stratification of naturally-occurring gene expression patterns and encompass different functional pathways and patient outcomes. Patients may have incurred different mutations and alterations that led to the different subtypes. We hypothesized that the LAD molecular subtypes co-occur with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
334
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(360 citation statements)
references
References 49 publications
26
334
0
Order By: Relevance
“…The role of HMGA2 in lung cancer prognosis was evaluated in lung adenocarcinoma patients, who were treated with CDDP based chemotherapy. To more accurately test the correlation between HMGA2 level and the patients' survival rate, we applied published microarray data 22 in GEO database (GSE36471) and calculated the Kaplan-Meier survival curve by DRUGSURV. 23 The results showed that patients with higher levels of HMGA2 expression had significantly lower survival probability than those with lower levels of HMGA2 expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of HMGA2 in lung cancer prognosis was evaluated in lung adenocarcinoma patients, who were treated with CDDP based chemotherapy. To more accurately test the correlation between HMGA2 level and the patients' survival rate, we applied published microarray data 22 in GEO database (GSE36471) and calculated the Kaplan-Meier survival curve by DRUGSURV. 23 The results showed that patients with higher levels of HMGA2 expression had significantly lower survival probability than those with lower levels of HMGA2 expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In both the discovery and TCGA cohorts, the epitypes were associated with the reported bronchioid (ES5), magnoid (ES1, ES2), and squamoid (ES4) adenocarcinoma gene expression phenotypes (9) (Fig. 3D).…”
Section: Adenocarcinoma Epitypes Are Associated With Adenocarcinoma Gmentioning
confidence: 96%
“…These expression modules included an immune response, a neuroendocrine, and a stroma/extra cellular matrix module. Data processing steps, including adenocarcinoma and SqCC molecular subtype classification (9,21), correlation of methylation and expression data, and calculation of different expression metagenes are further described in Supplementary Materials and Methods.…”
Section: Global Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, bronchioid tumors harbor EGFR mutations and tyrosine kinase (TK) fusions more frequently than other subtypes, are seen more frequently in never-smokers and associated with better prognosis. When applied to tumor samples that were a part of the JBR.10 trial, which demonstrated benefit with adjuvant cisplatin and vinorelbine in early-stage NSCLC, this classification system demonstrated that only magnoid subtype tumors showed a significant disease-free survival benefit with adjuvant therapy [10]. It is speculated that magnoid tumors, which show a high degree of chromosomal instability compared with other subtypes, harbor DNA repair pathway defects that render them more sensitive to platinum therapy.…”
Section: Molecular Classification Of Lung Adenocarcinomamentioning
confidence: 99%